2021
DOI: 10.3390/medicina57090919
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum and Pneumothorax as Relevant Complications of Sub-Intensive Care of Patients with COVID-19: Description of a Case Series

Abstract: Lung failure has been the most common cause of hospitalization for COVID-19. Yet, bilateral interstitial pneumonia has not been the only cause of lung failure of these inpatients, and frequently they develop other illnesses associated with COVID-19. Pulmonary embolism has been the most looked for in the world, but rarely other pneumological diseases, such as pneumothorax and pneumomediastinum, have been described and associated with a worsening prognosis. We here report our clinical experience associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Coppola et al reported their experience in six cases of pneumomediastinum and one case of pneumothorax during treatment in a sub-intensive area of the division of medicine [33]. In this series, four patients had pneumomediastinum and SCE following NIV.…”
Section: Discussionmentioning
confidence: 64%
“…Coppola et al reported their experience in six cases of pneumomediastinum and one case of pneumothorax during treatment in a sub-intensive area of the division of medicine [33]. In this series, four patients had pneumomediastinum and SCE following NIV.…”
Section: Discussionmentioning
confidence: 64%
“…In rare cases, spontaneous PMS was associated with PTX [ 123 ]. The prevalence of these conditions increased during the second wave of the pandemic with the increasing use of oxygen through non-invasive ventilation and steroid therapy [ 118 , 121 , 122 , 123 , 124 , 125 , 126 ]. The high airway pressures delivered by these modalities of respiration probably supported the spontaneous rupture of fragile small airways infected by the virus ( Figure 17 and Figure 18 ).…”
Section: Lung Complicationsmentioning
confidence: 99%
“…The identification of several clinical conditions that represent risks of mortality for patients affected by COVID-19 [ 6 , 7 ], including the identification of several laboratory markers [ 8 , 9 ] that may play similar roles, attracted the attention of all workers in emergency departments. Furthermore, rare complications of treatments for COVID-19, such as spontaneous or ventilation-induced pneumothorax, pneumopericardium, or pneumopericardium, acquired great relevance during the outbreak [ 10 , 11 ]. Moreover, emergency departments adapted their activities to identify and manage the severe complications of vaccinations against SARS-CoV-2, such as vaccine-induced thrombocytopenia with thrombosis [ 12 ].…”
mentioning
confidence: 99%